Circular Economy Model through Using Aquaponic Technology to Support the ProKlim Village Program in RT 10 Petukangan Utara, Jakarta - Martini; Yousep Eka Irawan Apriandi; Rismawandi; Windarto (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This community service program supports the ProKlim (Program Kampung Iklim) initiative in RT 10 Petukangan Utara, South Jakarta by implementing a circular economy model through integrated tilapia (Oreochromis niloticus) and Pak coy (Brassica rapa var. chinensis) cultivation using aquaponic technology. Designed for densely populated urban areas with limited land, the aquaponic system converts fish waste into plant nutrients while plants purify the water, creating a closed-loop, zero-discharge process. The program consisted of awareness sessions, technical training, installation of aquaponic units, and community mentoring. Program outcomes indicate substantial improvements in environmental knowledge, climate adaptation awareness, and sustainable food-production skills. The system achieved 78–82% water savings, significantly reducing resource consumption compared to conventional methods. Pre- and post-training assessments showed a 90% increase in participants’ understanding of aquaponics and circular economy principles. Each production cycle generated 20 kg of Pak coy and 10 kg of tilapia, contributing to household nutrition and providing IDR 400,000–600,000 in additional microeconomic value through consumption and local sales. These quantitative results validate the effectiveness of aquaponic-based circular economy practices in supporting ProKlim objectives, particularly in enhancing climate adaptation, promoting sustainable resource use, and strengthening community empowerment in limited urban spaces.